H2B monoubiquitination: t'ub or not t'ub for inducible enhancers. Issue 2 (15th March 2017) - Segala, Gregory; Picard, Didier
ABSTRACT: Recently, we reported the unexpected finding that the monoubiquitination of histone H2B (H2Bub1) regulates inducible enhancers. Here, we propose a conceptual framework to reconcile the apparently discrepant roles of H2Bub1 in transcription initiation and elongation, and we discuss how H2Bub1 could regulate cellular processes linked to non-coding transcription.